2002
DOI: 10.1007/s00134-002-1418-z
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine-phosphate-guanine (CpG) motifs are sensitizing agents for lipopolysaccharide in toxic shock model

Abstract: Our findings indicate that CpG motifs act synergistically with LPS by initializing the synthesis of TNF-alpha and/or TNF-alpha regulating factors, thereby acting as a sensitizing agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 46 publications
3
42
0
Order By: Relevance
“…In this model system, administration of immunostimulatory CpG ODN reduced survival (Fig. 1C), a finding consistent with the ability of CpG DNA to synergistically enhance LPS-induced cytokine production (29,30).…”
Section: Suppressive Odn A151 Protects Mice From Lps-induced Endotoxisupporting
confidence: 79%
“…In this model system, administration of immunostimulatory CpG ODN reduced survival (Fig. 1C), a finding consistent with the ability of CpG DNA to synergistically enhance LPS-induced cytokine production (29,30).…”
Section: Suppressive Odn A151 Protects Mice From Lps-induced Endotoxisupporting
confidence: 79%
“…Klebsiella. Importantly, although potentially beneficial in systemic infections, deleterious effects can occur when bacterial DNA or CpG ODN is administered in a systemic fashion (3,21,36,37). In our model, the compartmentalized delivery of CpG ODN was well tolerated and may be preferable to systemic delivery methods when protecting against respiratory pathogens.…”
Section: Discussionmentioning
confidence: 86%
“…On the other hand, Table 2 Bile flow and liver enzyme activities at 6 and 16 h after LPS-exposure in control-ODN-and CpG-ODN pre-treated animals Bile flow (ml/min g) AST (U/L) ALT (U/L) LDH (U/L) Values are given as meanGSEM. others have shown that the synergistic enhancement of LPSmediated TNF-a production by CpG-ODN [26][27][28] increases the toxicity and mortality after endotoxin exposure [16,28,29]. However, CpGs, in particular if applied before LPS stimulation, have also been shown to be capable of reducing LPS-mediated NFkB activation [30] and TNF-a production in vitro [31,32], and minimizing LPS-induced inflammation in the lower respiratory tract in vivo [33].…”
Section: Discussionmentioning
confidence: 98%